The Role of Dectin-1-Akt-RNF146 Pathway in β-Glucan Induced Immune Trained State of Monocyte in Sepsis - Guo C; Xu P; Luo W; Zhang J; Sun X; Hoang H; Ma D; Wu D; Zhong J; Miao C (Journal of Inflammation Research)
Chenyue Guo,1,* Peiyao Xu,1,* Wenchen Luo,1,* Jinlin Zhang,1,* Xingfeng Sun,2 Harry Hoang,3 Duan Ma,4 Dehua Wu,5 Jing Zhong,1 Changhong Miao1 1Department of Anesthesiology, Zhongshan Hospital Fudan University, Fudan University Shanghai Cancer Center, Department of Oncology, Shanghai Medical College, Fudan University, Shanghai Key Laboratory of Perioperative Stress and Protection, Shanghai, People’s Republic of China; 2Department of Anesthesiology, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, People’s Republic of China; 3Lausanne University Hospital and University of Lausanne, Lausanne, Switzerland; 4Key Laboratory of Metabolism and Molecular Medicine, Ministry of Education, Department of Biochemistry and Molecular Biology, Collaborative Innovation Center of Genetics and Development, Institute of Biomedical Sciences, School of Basic Medical Sciences, Fudan University, Shanghai, People’s Republic of China; 5Department of Anesthesiology, Shanghai Songjiang District Central Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Changhong Miao; Jing Zhong, Email ziteng1934@aliyun.com; jzhong12@fudan.edu.cnBackground: Sepsis is regarded as a dysregulated immune response to infections. Recent study showed partially reversal of immunosuppression by trained immunity, which fosters an enhanced immune response towards a secondary challenge. However, the role of trained immunity in sepsis has not been fully understood.Methods: We profiled the characteristics of peripheral blood mononuclear cells from septic patients using single-cell RNA sequencing (scRNA-seq) analyses. Murine double-hit models (pretreatment or post-treatment of β-glucan in septic mice) and murine monocyte/macrophage cell line RAW264.7 were used then.Results: scRNA-seq revealed that Ring finger protein 146 (RNF146) and protein kinase B (Akt) were downregulated in the immunosuppression period of septic patients and were verified to be decreased in bone marrow and spleen monocytes from septic mice. While β-glucan pretreatment improved the immunosuppressed state in septic mice and increased dectin-1/Akt/RNF146 expressions in monocytes, along with the increased survival rate, inflammatory factors and aerobic glycolysis, indicating a change from immunosuppression to immune training. Moreover, RNF146 regulated dectin-1-Akt-mTOR signaling in the trained immune state of murine monocyte/macrophage RAW264.7 cell line and the expression of RNF146 was dependent on dectin-1-Akt activation. The inhibition of dectin-1 by its antagonist laminarin downregulated Akt-RNF146 signaling and partially reversed β-glucan induced trained immunity in septic mice.Conclusion: RNF146 and Akt are downregulated in the immunosuppression period of sepsis, while increased after β-glucan pretreatment induced trained immunity in septic mice. Moreover, RNF146 regulates the immune trained state of monocyte through dectin-1-Akt-mTOR pathway, suggesting a possible target in reversal of immunosuppression in sepsis.Keywords: RNF146, β-glucan, trained immunity, immunosuppression, sepsis